Using Problem-Solving Therapy to Reduce Depressive Symptom Severity Among Older Adult Methadone Clients: A Randomized Clinical Trial. (October 2018) - Rosen, Daniel; Engel, Rafael; McCall, Janice; Greenhouse, Joel
Objective: Treatment of older adults in methadone maintenance treatment (MMT) with comorbid mood disorders presents many challenges. The goal of this randomized controlled trial was to assess the combined effect of problem-solving therapy (PST) with treatment as usual (TAU) compared to TAU alone on decreasing depressive symptoms in opioid-addicted older adults in MMT. Methods: Sixty-four methadone clinic attendees, at least 50 years old, with moderate depressive symptom were randomized to PST + TAU ( n = 29) or TAU ( n = 35). PST is an intervention for depressed older adults with a focus on teaching problem-solving skills. Results: There was not a statistically significant difference in depression scores between the two treatment groups. However, there is evidence for a clinically meaningful decrease in symptoms in the PST + TAU group 7 months post treatment (Cohen's d = .57) Conclusion: Clinical implications of PST + TAU in comparison to TAU on depressive symptom seemed to have lasting benefits at 6-month post treatment.